The flawed family of God: stories about the imperfect families of Genesis - Helsel, Carolyn Browning (Westminster John Knox Press, 2021)
"This Bible study examines the families of Genesis, starting with how the Adam and Eve story encompasses far more ways of being family-including singleness-than most of us think, and shows us that the ups and downs of the relationship between Abraham, Sarah, Hagar, and Ishmael can help us understand the complicated dynamic of blended families"--